Digital platforms regulation and the challenges for urban policies: An exploratory study in the city of Lisbon - Costa, P. (33th RESER International Conference “Digital Transformation and the Service Economy: Exploring the Societal Impact”, 2023)
OBJECTIVES: Around the world we have witnessed over the last few years a significant increase in a wide range of urban externalities induced by the development of the platform economy and the digitalisation of some consumer services, in particular in fields such as distribution, deliveries, light mobility, accommodation, tourism, co-working, content services platforms, among others. Regulation has not been able to respond efficiently to these dynamics, and there is a need to adapt governance and regulatory mechanisms to these new realities, from urban planning and the licensing and regulation of these activities to the spheres of the labor market, training policies or international mobility. In this paper we address specifically the urban impacts of these transformations, and the need of a regulatory framework at urban/ metropolitan level, focusing on the particular case of Lisbon in Portugal. In effect, the changes brought by algorithms and platform-based activities, in fields such as mobility applications (e.g., transportations services, ride-sharing, public and private light mobility platforms - bikes, scooters, etc. -, urban delivery – of food and increasingly other goods -, international distribution and e-commerce, travel, accommodation and tourism, short, medium and long term housing rentals, offices and co-working spaces, among other domains, have been bringing new conflicts to the urban space, in a diversity of arenas, both material and symbolic (crossing public space appropriation, gentrification trends, labor market structuring, or immigration and international mobility policies), which are clearly visible in a series of external effects and tensions (from congestion and overload to competition through market and other mechanisms) that have been recurrently reported as affecting particularly (but not exclusively) historical centers and urban central areas. Local authorities have difficulty to deal and to adapt to this situation and to identify the new challenges they are facing as well as tools to deal with global mechanisms and technological structures of which they have no great knowledge and with whom they have no great power to act effectively. Therefore, it is important to reflect on and respond to this need for policies and planning, which can make it possible to mitigate these externalities and their negative effects on the daily lives of the populations of these cities. In this paper we analyze these dynamics and identify some challenges in terms of regulation and public policies, for the specific case of Lisbon. After an introductory section, contextualizing the work, its framework and some methodological aspects, section 2 deals with conceptual issues related to the expansion of platform economy and its impacts on urban space, with particular emphasis on the provision of consumer services. Section 3 identifies the main challenges and problems that this relation of platform economy with territorial organization brings to urban planning and urban development, based on the analysis and the creation of typologies for specific platform services. Section 4 assesses the specific case of Lisbon, as an example of these challenges in practice and its implications in regulatory terms. Particular emphasis is put in the specific cases of ridesharing, light shared mobility and deliveries, focusing on the urban externalities induced by the digital shift in these sectors. Finally, a concluding session identifies a set of challenges and fields for public action, concerning the regulation of the conflicts and the needs for balance regarding uneven power associated to these changes. METHODOLOGY The analysis conducted in this paper is essentially based on desk research, considering the exploratory character of this work. On one hand, a review on literature on platform economy and its relation with urban space and territorial dynamics is conducted; on the other hand, an analysis of the existing empirical works on specific digital platforms activities’ impacts in the metropolitan area of Lisbon is developed. This work is complemented with direct observation and mobilization of author’s specific know-how on the dynamics of central Lisbon, fruit of a diversity of research projects which had this area as empirical object during recent years. Based on this conceptual and empirical results achieved, it will be identified and systematized a set of challenges that Lisbon is facing concerning regulatory needs and policy orientation. The exploratory work presented in this paper will be the basis for future further work, involving interviews to main stakeholders, in order to identify specific policy guidelines. EXPECTED RESULTS: This paper will present a framework for the analysis of urban externalities induced by digitalization and platform economies, regarding consumer services, and will identify a typology of challenges brought by these recent changes for governance and public action at urban level. The analyses conducted for the specific case study of Lisbon (focused on the particular cases of ridesharing, light shared mobility and deliveries) will enable us to identify particular regulation challenges and fields of action, in order to empower local authorities for facing the rise on urban externalities and on urban conflict, and to prepare further work on the definition of specific policy guidelines. Bibliography Rodrigues, N; Vale, M.; Costa, P. (2022) Urban experimentation and smart cities: a Foucauldian and autonomist approach, Territory, Politics, Governance, 10:4, 549-567 Rodrigues, N.; Costa, P (2022) “Práticas Espaciais Digitalmente Mediadas: conceptualização e problematização das práticas espaciais dos trabalhadores de plataformas de Ride-Sharing e Food-Delivery”, in Gato, M. A. e Guibentif, P. (coords) “Entre Transições: Retrospetivas – Transversalidades- Perspetivas”, Lisboa: DINÂMIA’CET-iscte, pp. 22-30 van Doorn, N., Ferrari, F., & Graham, M. (2023). Migration and Migrant Labour in the Gig Economy: An Intervention. Work, Employment and Society, 37(4), 1099–1111. Stehlin, J., Hodson, M., & McMeekin, A. (2020). Platform mobilities and the production of urban space: Toward a typology of platformization trajectories. Environment and Planning A: Economy and Space, 52(7), 1250-1268. Costa, P. (2023), “Das políticas sectoriais a uma política integrada de desenvolvimento local: reflexões a partir do caso do centro histórico lisboeta”, in Teixeira, A.; Delgado, A. P.; Carvalho, L.; Mota, M. I; Castro e Silva, M. M. (orgs.), Estudos de Homenagem a José da Silva Costa, Porto: Faculdade de Economia da U.Porto (FEP), U.Porto Press, pp. 722-739